2010
DOI: 10.1177/0891988710373598
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Inflammatory Markers and Post Stroke Cognitive Impairment

Abstract: A post stroke inflammatory response may be important in subacute, PSCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 41 publications
4
81
0
5
Order By: Relevance
“…Deep white matter hyperintensities are more frequently due to cerebral ischemia, and such ischemic lesions are more frequently located at the level of dorsolateral prefrontal cortex in depressed subjects [52]. Baseline concentrations of intercellular Adhesion Molecule 1 (ICAM-1) have also been shown to predict increased white matter hyperintensities (WMH) burden on 3-and 6-year follow-up [53]. Thus, neopterin may contribute to the development of depression via an increased WMH burden, mediated in part by its contributions to the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 98%
“…Deep white matter hyperintensities are more frequently due to cerebral ischemia, and such ischemic lesions are more frequently located at the level of dorsolateral prefrontal cortex in depressed subjects [52]. Baseline concentrations of intercellular Adhesion Molecule 1 (ICAM-1) have also been shown to predict increased white matter hyperintensities (WMH) burden on 3-and 6-year follow-up [53]. Thus, neopterin may contribute to the development of depression via an increased WMH burden, mediated in part by its contributions to the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 98%
“…Limited data have shown that elevated levels of some inflammatory markers in the circulation of ischemic stroke patients imply a lower grade of poststroke global cognition (7).…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of cytokines could result in disruption of hippocampal function and hippocampal neurodegeneration [39]. Studies of TLR4-deficient mice suggest that TLR4 signaling has a negative impact on hippocampus-dependent cognitive function [40].…”
Section: Discussionmentioning
confidence: 99%